Simplex cerebral cavernous malformations with MAP3K3 mutation have distinct clinical characteristics - Huo, Ran; Wang, Jie; Sun, Ying-Fan; Weng, Jian-Cong; Li, Hao; Jiao, Yu-Ming; Xu, Hong-Yuan; Zhang, Jun-Ze; Zhao, Shao-Zhi; He, Qi-Heng; Wang, Shuo; Zhao, Ji-Zong; et al. (Frontiers in Neurology, 2022)
Objectives To investigate the clinical characteristics of cerebral cavernous malformations (CCMs) with MAP3K3 somatic mutation. Methods We performed a retrospective review of our CCMs database between May 2017 and December 2019. The patients with simplex CCMs identified to harbor a MAP3K3 or CCM gene somatic mutation were included. Clinical characteristics were recorded. Univariate and multivariate logistic analyses were used to assess the risk factors associated with hemorrhage events of CCMs. To explore the underlying mechanism, we transfected MEKK3-I441M-overexpressing and CCM2-knockdown lentiviruses into human umbilical vein endothelial cells (HUVECs) and investigated thrombomodulin (TM) and tight junctions (TJs) protein expression by western blotting and immunofluorescence. Finally, immunohistochemistry was used to validate TM and TJs protein expression in surgical samples. Results Fifty simplex CCMs patients were included, comprising 38 MAP3K3 mutations and 12 CCM gene mutations. Nine (23.7%) patients with MAP3K3 mutations and 11(91.7%) patients with CCM gene mutations exhibited overt hemorrhage, respectively. Multivariate logistic analyses revealed that MAP3K3 mutation was associated with a lower risk of hemorrhage events. In the vitro experiments, ZO-1 expression was not reduced in MEKK3-I441M-overexpressing HUVECs compared with wild type, whereas it was significantly decreased in CCM2-knockdown HUVECs compared with control. In the MEKK3-I441M-overexpressing HUVECs, TM expression was increased, and the NF-κB pathway was significantly activated. After treatment with an NF-κB signaling inhibitor, TM expression was further upregulated. Meanwhile, TM expression was increased, but the NF-κB pathway was not activated in CCM2-knockdown HUVECs. Accordingly, immunohistochemistry showed that ZO-1 expression in the MAP3K3-mutant samples was significantly higher than that in the CCM-mutant samples. TM expression in the MAP3K3-mutant lesions was significantly lower than that in the CCM-mutant samples. Conclusion Simplex CCMs with MAP3K3 mutation occasionally present with overt hemorrhage, which is associated with the biological function of MAP3K3 mutation.